2014
DOI: 10.14740/jem237w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Alveolar Bone Mandibular of Rats Obese Induced at Monosodium Glutamate Undergoing Modified Duodenal-Jejunal Bypass Surgery

Abstract: Background: Obesity is a worldwide epidemic and its prevalence has doubled in recent years. Studies report that obesity may positively or negatively influence on bone mass resulting in formation or resorption. Furthermore, there is evidence suggesting that some obesity surgical treatments can also result in bone resorption. Thus, the aim of this study was to determine the consequences of monosodium glutamate (MSG)-induced obesity and modified duodenaljejunal bypass (modDJB) surgery on the mandibular alveolar b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Therefore, it may be inferred that obesity alone did not cause notable structural changes in periodontal tissues. These results corroborate the morphological findings obtained by Felipetti et al [22]; however, it must be emphasized that the obesity induction in our study was exogenous, whereas it was endogenous in the previous study. Moreover, it was verified that obesity alone, not associated with EP, was not able to influence greater alveolar bone loss, which confirmed the histological data.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, it may be inferred that obesity alone did not cause notable structural changes in periodontal tissues. These results corroborate the morphological findings obtained by Felipetti et al [22]; however, it must be emphasized that the obesity induction in our study was exogenous, whereas it was endogenous in the previous study. Moreover, it was verified that obesity alone, not associated with EP, was not able to influence greater alveolar bone loss, which confirmed the histological data.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings corroborate these studies and showed that the hypercaloric diet was able to induce weight gain in the animals tested compared with animals fed standard animal food. This approach has been a good model for the induction of exogenous obesity, whereas endogenous obesity may be induced by other experimental models, such as the subcutaneous injection of monosodium glutamate; however, this method may generate conditions that are not ideal for investigations of the development and progression of periodontal disease [22]. Other authors have also assessed EP in models with obese Zucker rats that bear a recessive autosomal mutation for the leptin receptor gene, which causes chronic hyperphagia and morbid obesity [12].…”
Section: Discussionmentioning
confidence: 99%